Genome-resolved metagenomics of an autotrophic thiocyanate-remediating microbial bioreactor consortium. (1st July 2019) - Watts, Mathew P.; Spurr, Liam P.; Lê Cao, Kim-Anh; Wick, Ryan; Banfield, Jillian F.; Moreau, John W.
Abstract: Industrial thiocyanate (SCN − ) waste streams from gold mining and coal coking have polluted environments worldwide. Modern SCN − bioremediation involves use of complex engineered heterotrophic microbiomes; little attention has been given to the ability of a simple environmental autotrophic microbiome to biodegrade SCN − . Here we present results from a bioreactor experiment inoculated with SCN − -loaded mine tailings, incubated autotrophically, and subjected to a range of environmentally relevant conditions. Genome-resolved metagenomics revealed that SCN − hydrolase-encoding, sulphur-oxidizing autotrophic bacteria mediated SCN − degradation. These microbes supported metabolically-dependent non-SCN - -degrading sulphur-oxidizing autotrophs and non-sulphur oxidizing heterotrophs, and "niche" microbiomes developed spatially (planktonic versus sessile) and temporally (across changing environmental parameters). Bioreactor microbiome structures changed significantly with increasing temperature, shifting from Thiobacilli to a novel SCN − hydrolase-encoding gammaproteobacteria. Transformation of carbonyl sulphide (COS), a key intermediate in global biogeochemical sulphur cycling, was mediated by plasmid-hosted CS2 and COS hydrolase genes associated with Thiobacillus, revealing a potential for horizontal transfer of this function. Our work shows that simple native autotrophic microbiomes from mine tailings can be employed for SCN − bioremediation, thus improving the recycling of ore processing waters and reducing the hydrological footprint of mining. Graphical abstract: Image 1 Highlights: SCN − hydrolase-encoding, S-oxidizing autotrophic bacteria mediated SCN − degradation. "Niche" microbiomes developed spatially (planktonic versus sessile) and temporally. Bioreactor microbiome structures changed significantly with increasing temperature. Transformation of COS was mediated by plasmid-hosted CS2 and COS hydrolase genes.